Twenty-First Century Trends in Girls’ Violence and the Gender Gap: Triangulated Findings from Official and Unofficial Longitudinal Sources - Steffensmeier, Darrell J. (Journal of interpersonal violence, 2023)
Recent media and academic reports project rising levels of girls’ violence and a narrowing gender gap. In response, the authors investigate 21st century trends in girls’ violence as reported across multiple official and unofficial longitudinal sources: Uniform Crime Reports (UCR) arrest and juvenile court referral statistics; National Crime Victimization Survey (NCVS) victimization data; and three sources of self-reported violent offending—Monitoring the Future, Youth Risk Behavior Surveillance System, and National Survey on Drug Use and Health. Augmented Dickey-Fuller time-series tests and intuitive plot displays show much overlap in each source’s portrayal of trends in girls’ violence and the youth gender gap. Specifically, there is no systematic change in the gender gap for homicide, aggravated assault, nor the violent crime index. However, UCR police arrests and juvenile court referrals show a moderate female-to-male rise for simple assault during the early decades of the 21st century. This rise in official statistics is not borne out in NCVS counts based on victims’ reports nor in self-reported violent-offending counts. Net-widening policy shifts and more gender-neutral enforcement have apparently elevated somewhat the arrest proneness of adolescent females for simple assault. Rather than girls having become more violent, triangulating data sources revealed a decline in both girls’ and boys’ violence levels, considerable similarity in their violent-offending trends, and little or no systematic change in the gender gap.